La cláusula de no-discriminación en la Decisión 578: ¿Un laberinto sin salida? - Liendo Tejada, Jorge (2021)
In this article, the author develops the problems in the application of Decision 578 in the pronouncements of the Peruvian Tax Administration and concludes that there is a need to explore and give greater content to the relationship between the legal system of the Andean Community and the Decision 578, since the latter is usually studied in isolation and seen as “another treaty” to avoid double taxation.